Ballistic response of ultra-high molecular weight polyethylene laminate impacted by mild steel core projectiles. (November 2022) - He, Yemao; Jiao, Yanan; Zhou, Johnny Qing; Lei, Hongshuai; Jia, Nan; Chen, Li; Zhang, Diantang
Highlights: Industrial X-ray computer tomography (ICT) was used to quantify internal damage in the post-impact ultra-high molecular weight polyethylene (UHMWPE) fiber composite laminate impacted by mild steel core projectiles. The progressive ballistic damage process of UHMWPE fiber composite laminate impacted by mild steel core projectile was elucidated. An evaluation model of the energy absorption by UHMWPE fiber composite laminate has been established to analyze the dissipation mechanism of projectile kinetic energy. Abstract: This paper presents the effect of interlaminar shear property on the ballistic response of ultra-high molecular weight polyethylene (UHMWPE) fiber composite laminate and discusses the detailed progressive ballistic damage process. Specifically, two kinds of UHMWPE fiber composite laminates with different interlaminar shear strength (ILSS) are impacted by a standard projectile (7.62 mm × 39 mm), and their multi-scale internal damage morphologies are characterized. Based on damage patterns, an evaluation model of laminate energy absorption is established to analyze the dissipation mechanism of the kinetic energy of the projectile. Results of ballistic tests indicate that the reduction of ILSS may result in the degradation of anti-penetration performance and in more serious internal damage. Internal damage morphologies show that shear fracture and delamination fracture are the primary failure modes during ballistic impact. The energy absorption by the laminate via tensile deformation, delamination failure and shear failure may account for 56.21%, 17.45%, and 16.49% of the projectile kinetic energy, respectively. Hence, tensile deformation may be the primary energy dissipation mechanism of projectile kinetic energy. Graphical abstract: Image, graphical abstract